Application of Safeguards and Anti-Dumping Duties in Colombia - Reina, Mauricio; Zuluaga, Sandra (World Bank, Washington, DC, 2012)
Colombia's experience in the use of safeguards and antidumping duties differs from international trends. On the one hand, the number of investigations conducted is substantially lower than that recorded in most of the hemisphere's large and medium-size countries. On the other hand, while there is a growing international trend of more frequent use of antidumping as opposed to safeguards, in Colombia the safeguard process has been the more used policy instrument. Although several large and medium-size firms are familiar with the application of safeguards and antidumping duties, there is still a relative unfamiliarity regarding the instruments in most of the private sector. The institutional arrangements related to the investigations and the decisionmaking processes have proven to be stable and sound. The trade liberalization process in the country has created awareness of the importance of preserving the competitiveness of production chains to strengthen their insertion in international markets, which has restrained the authorities from restricting access to intermediate goods and raw materials. The evaluation of the Colombian experience also raises concerns about the potential discretional use of these instruments. The relatively intense use of safeguards and antidumping measures in some specific periods and sectors, especially in the agricultural sector, shows that the institutional framework is not always enough to guarantee a disciplined use of the instruments.